Photophobia as a result of ocular and neuronal mechanisms: pathophysiology and clinical implications - Milewska, Kamila; Fabis, Katarzyna; Byjos, Ewa; Zbylut, Mateusz; Buczek, Sylwia; Mstowska, Weronika; Bury, Karolina; Naliuka, Hanna; Młynarczyk, Katarzyna; Mateja, Patrycja (Journal of Education, Health and Sport, 2026)
Background: Photophobia is a common symptom across a wide range of neurological and ophthalmological disorders that might be defined as an abnormal aversion or sensitivity to light. Despite its prevalence, the clinical spectrum and underlying pathophysiological mechanisms remain incompletely understood. Aim of the review: The present study was aimed at summarizing and comparing data from available literature regarding the current evidence on the conditions associated with photophobia and to clarify the mechanisms contributing to light sensitivity. Methods: This narrative review was conducted through a structured literature search of the PubMed database covering publications from January 2000 to March 2025. Additional relevant articles were identified through manual screening of reference lists. Eligible articles were selected based on predefined criteria and synthesized narratively due to the heterogeneity of study designs. Results: Photophobia was mostly associated with migraine, ocular surface disease, retinal disorders, and traumatic brain injury. Across studies, light sensitivity was linked to interactions between intrinsically photosensitive retinal ganglion cells, trigeminal nociceptive pathways, and thalamocortical processing networks. The reviewed literature also highlighted considerable variability in clinical presentation, reflecting the diverse mechanisms contributing to photophobia across different conditions. Conclusions: Photophobia is a multifaceted symptom arising from complex interactions between retinal, trigeminal, and central neural pathways. A deeper understanding of its neurobiological mechanisms and broad clinical spectrum enables clinicians to make more accurate diagnoses and to develop targeted interventions for diverse patient populations.